Investigations of potential microbial methanogenic and carbon monoxide utilization pathways in ultra-basic reducing springs associated with present-day continental serpentinization: the Tablelands, NL, CAN - Morrill, Penny L.; Brazelton, William J.; Kohl, Lukas; Rietze, Amanda; Miles, Sarah M.; Kavanagh, Heidi; Schrenk, Matthew O.; Ziegler, Susan E.; Lang, Susan Q. (Frontiers in Microbiology, 2014)
Ultra-basic reducing springs at continental sites of serpentinization act as portals into the biogeochemistry of a subsurface environment with H2 and CH4 present. Very little, however, is known about the carbon substrate utilization, energy sources, and metabolic pathways of the microorganisms that live in this ultra-basic environment. The potential for microbial methanogenesis with bicarbonate, formate, acetate, and propionate precursors and carbon monoxide (CO) utilization pathways were tested in laboratory experiments by adding substrates to water and sediment from the Tablelands, NL, CAD, a site of present-day continental serpentinization. Microbial methanogenesis was not observed after bicarbonate, formate, acetate, or propionate addition. CO was consumed in the live experiments but not in the killed controls and the residual CO in the live experiments became enriched in 13C. The average isotopic enrichment factor resulting from this microbial utilization of CO was estimated to be 11.2 ± 0.2‰. Phospholipid fatty acid concentrations and δ13C values suggest limited incorporation of carbon from CO into microbial lipids. This indicates that in our experiments, CO was used primarily as an energy source, but not for biomass growth. Environmental DNA sequencing of spring fluids collected at the same time as the addition experiments yielded a large proportion of Hydrogenophaga-related sequences, which is consistent with previous metagenomic data indicating the potential for these taxa to utilize CO.